CTNNB1 syndrome (CTNNB1-NDD) in a child with cerebral palsy: a case report - G. S. Golosnaya; N. A. Ermolenko; O. N. Krasnorutskaya; V. L. Efimova; T. A. Larionova; M. D. Tysyachina (Русский журнал детской неврологии)
In this article, we report a case of CTNNB1 syndrome (CTNNB1-NDD) in a child with cerebral palsy and also provide a literature review on the problem. CTNNB1 syndrome is an exceedingly rare and poorly studied disorder, which makes it particularly interesting due the difficulties associated with its diagnosis and description of the disease phenotype, as well as highly polymorphic clinical manifestations. Verification of the diagnosis is important to determine the prognosis of a child with cerebral palsy and visual impairment, as well as for reproductive planning in the family.